Multinational Business Finance / Third Edition - Eiteman David K; Stonehill Arthur I (,́, 1982)
The Multinational Corporation and Its International Environment, The Multinational Firm: Its Rationale and Goals and Constraints, International Monetary System, Foreign Exchange Market, Foreign Exchange Risk Management, Forecasting Foreign Exchange Rates, Measuring Foreign Exchange Exposure, Managing Foreign Exchange Exposure, Long-Run Investment Decisions, The Foreign Investment Decision, Political Risk Management, Multinational Capital Budgeting, Financing Decisions, 10 International Financial Markets, Cost of Capital and Financial Structure, International Banking, Working Capital Management, Positioning of Funds, Current Asset Management, Control, Organization and Performance Evaluation, International Accounting, Tax Planning, Bibliography, Author and Subject Index.
The Multinational Corporation and Its International Environment, The Multinational Firm: Its Rationale and Goals and Constraints, International Monetary System, Foreign Exchange Market, Foreign Exchange Risk Management, Forecasting Foreign Exchange Rates, Measuring Foreign Exchange Exposure, Managing Foreign Exchange Exposure, Long-Run Investment Decisions, The Foreign Investment Decision, Political Risk Management, Multinational Capital Budgeting, Financing Decisions, 10 International Financial Markets, Cost of Capital and Financial Structure, International Banking, Working Capital Management, Positioning of Funds, Current Asset Management, Control, Organization and Performance Evaluation, International Accounting, Tax Planning, Bibliography, Author and Subject Index.